THE FACTORS RELATED TO THE POSTPARTUM MOTHERS’ KNOWLEDGE OF THE PUBLIC ABOUT THE DANGER SIGNS OF PUERPERIUM AT PMB LISMARINI PALEMBANG - Harista, Junie (Masker Medika, 2020)
THE FACTORS RELATED TO THE POSTPARTUM MOTHERS’ KNOWLEDGE OF THE PUBLIC ABOUT THE DANGER SIGNS OF PUERPERIUM AT PMB LISMARINI PALEMBANG ABSTRACT The puerperium is the period after childbirth 6 weeks or 42 days. During the puerperium, the reproductive organs will slowly experience changes like before pregnancy. This change in the reproductive organs is called involution (Dewi, 2017). During this time, a puerperal mother often has problems with signs of danger in puerperium including post partum hemorrhage, foul-smelling lochea, uterine subinvolution, abdominal and pelvic pain, excessive dizziness, maternal body temperature> 38 ̊C, mastitis, baby blues and postpartum depression. The puerperium is a critical period for mothers who have given birth. It is estimated that 60% of maternal deaths occur after delivery and 50% of them occur within the first 24 hours (Prawiharjo, 2010). The purpose of this study was to determine the factors related to the postpartum mothers’ knowledge about the danger signs of puerperium at Lismarini Midwife Independent Practice Palembang 2019. The design of this study was an analytical survey with a cross sectional approach. The population in this study were all postpartum mothers who visited at the time of the research at Lismarini Midwife Independent Practice. The sampling technique used Accidental Sampling totaling 36 mothers. The results showed that there was no relationship between the age of the postpartum mother and the knowledge about the danger signs of puerperium, obtained p value = 0.467> 0.05, there was no relationship between parity of the postpartum mother and knowledge about the danger signs of puerperium, obtained p value = 0.370> 0 , 05, there was a relationship between the education of postpartum mothers with knowledge about the danger signs of the puerperium, p value = 0.039 <0.05, and there was a relationship between the work of the postpartum mother and knowledge about the danger signs of puerperium was p value = 0.016 <0.05. It is expected to the health workers to improve information and education communication (IEC) about the dangers of puerperium in various media so that it can increase the mother's knowledge and understanding. Keywords : postpartum mother, danger signs of puerperium, knowledge, age, parity, education and occupation Bibliography : 15 (2010-2019)